You are here:

# Algebra/Algebra question system (12.7-1)

Question
I am told to solve the following system:
y = 2x^2 + 5x + 9
y = -4x + 5

The y = 2x^2 + 5x + 9 factors.
Since 2 is prime, try (2x+ )(x+ ).
Since the 9 is 3*3, try (2x+3)(x+3).
Sure enough, multiplying the right side on the equation y = (2x+3)(x+3)
gives y = 2x^2 + 5x + 9.

Assuming we are trying to get y = 0, we need to have either 2x+3 = 0 or x+3 = 0.
Subtracting 3 from both sides on both equations gives 2x = -3 and x = -3.

The 2nd equation is solved already, for it is just x=-3.

The 1st equation needs to be divided by 2 on both sides.
That gives x = -3/2.  This is the same as x = -1½.

Algebra

Volunteer

#### Scott A Wilson

##### Expertise

Any algebraic question you've got. That includes question that are linear, quadratic, exponential, etc.

##### Experience

I have solved story problems, linear equations, parabolic equations. I have also solved some 3rd order equations and equations with multiple variables.

Publications
Documents at Boeing in assistance on the manufacturiing floor.

Education/Credentials
MS at math OSU in mathematics at OSU, 1986. BS at OSU in mathematical sciences (math, statistics, computer science), 1984.

Awards and Honors
Both my BS and MS degrees were given with honors.

Past/Present Clients
Students in a wide variety of areas since the 80's; over 1,000 of them have been in algebra.